A novel dielectric sensor for process monitoring of carbon fibre composites manufacturing - Tifkitsis, Konstantinos; Skordos, Alexandros A. (Elsevier, 2019)
A dielectric sensor appropriate for process monitoring of composites manufacture with carbon reinforcement has been developed in this study. The sensor concept overcomes problems of electrical sorting and interference with the electric field occurring when electrical/dielectric sensors are used with carbon reinforcement. The sensor comprises two uniformly twisted insulated copper wires. Two sensor designs based on the same concept have been implemented; a lineal sensor for flow front position tracking and a woven sensor used to monitor the cure. Resin Transfer Moulding (RTM) processing has been employed to evaluate the lineal sensor performance against visual monitoring of the flow front. Vacuum Assisted RTM (VARTM) has been carried out to validate the results of the woven cure sensor against calorimetric cure kinetics models. Both the lineal flow and woven cure sensors provide accurate monitoring signals.
Keywords: Carbon fibres; Curing; Resin Transfer Moulding (RTM); Process monitoring